An integrative review of nursing leadership in Saudi Arabia - Bayan Alilyyani; Michael S. Kerr; Carol Wong; Dhuha Y. Wazqar (Wiley, 2022)
Abstract Aims The aims of this integrative review were to describe leadership styles from the nursing literature in Saudi Arabia and to identify the current state of evidence about relationships between leadership styles and nurse, patient and organization outcomes in Saudi Arabia. Design Integrative review was used as a design for this study. Methods The following search terms were used with databases: 'Saudi Arabia', 'leadership theory*', 'leadership style*', 'leadership model*', 'management style' and 'nurse*'. Methodological quality was assessed using two different quality rating tools for quantitative and qualitative studies. Databases used for this review included Nursing & Allied Health Database, Cochrane Database of Systematic Reviews, PubMed, CINAHL, Embase, PsycINFO, Scopus, Web of Science and ProQuest Dissertations & Theses. Results Nine manuscripts representing eight studies were included in this review. The papers reviewed included quantitative (n = 6), qualitative (n = 2) and mixed methods studies (n = 1). Results were grouped into different themes, identified as nursing leadership styles in Saudi Arabia, leadership styles and nurses' outcomes, and demographics and leadership styles.